“Discapacidad auditiva en el proceso de enseñanza-aprendizaje” - Tasinchana Maigua, Alex Santiago (2023)
The current society requires a quality education. Therefore, the teacher's work is increasingly demanding because teachers are responsible for the proper development of teaching and for deaf and hard-of-hearing students to acquire essential knowledge. In this aspect, the research project's objective is to analyze the teaching-learning process in children with hearing disabilities through sign language to strengthen reading-writing skills in elementary school students of the Cotopaxi Specialized Educational Unit, 2022-2023. The methodology applied was qualitative because it described the educational reality in the didactic process, as well as the interview technique and the interview guide, which allowed for the collection of information about the teaching-learning process in reading-writing skills that takes place in the classroom. The proposal is focused on creating a didactic guide to strengthen reading and writing skills through interactive activities, images, words, and phrases supported by sign language, which should be exposed in the Back to School program to motivate the student and improve the teaching and learning process.